Because Each Life is Precious : Why An Iraqi Man Risked Everything for Private Jessica Lynch - Odeh, Al-Rehaief, Mohammed and Coplon, Jeff (New York HarperCollins, 2003)
The Iraqi civilian who helped rescue Private First Class Jessica Lynch from her captors during the Iraq War recounts his ordeals living in Iraq, his motivations for helping Lynch, and details on how he managed to save her life.
Keywords: Iraq -- Iraq War (2003-2011) -- Lynch, Jessica, 1983-